2020
DOI: 10.3390/educsci10040113
|View full text |Cite
|
Sign up to set email alerts
|

Digital Teaching Materials and Their Relationship with the Metacognitive Skills of Students in Primary Education

Abstract: Metacognition is a construct that is noteworthy for its relationship with the prediction and enhancement of student performance. It is of interest in education, as well as in the field of cognitive psychology, because it contributes to competencies, such as learning to learn and the understanding of information. This study conducted research at a state school in the Community of Madrid (Spain) with a sample of 130 students in Grade 3 of their primary education (8 years old). The research involved the use of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 58 publications
0
12
0
2
Order By: Relevance
“…Some authors focus on positive effects on LD students’ attitude on learning, motivation and engagement, interest, active engagement, attention and on cooperative dynamics between students [ 39 , 40 , 42 , 44 ]. Other papers have described the effects of E-learning on general development and on learning path of students with LD (it equips students with LD with adequate skills to allow them to continue with further study through various pathways) [ 34 , 35 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some authors focus on positive effects on LD students’ attitude on learning, motivation and engagement, interest, active engagement, attention and on cooperative dynamics between students [ 39 , 40 , 42 , 44 ]. Other papers have described the effects of E-learning on general development and on learning path of students with LD (it equips students with LD with adequate skills to allow them to continue with further study through various pathways) [ 34 , 35 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hodges et al [ 31 ] describe emergency remote teaching as different from well-structured, systematic online learning. For example, communication with and feedback by teachers has been sporadic and difficult to obtain, although this is an essential part of effective online learning [ 32 ]. Recent studies on lockdown schooling confirmed that teachers as well as learners need training in handling new technologies and digital tools [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, with regard to sample recruitment, some authors chose samples consisting of different groups of students with other kinds of disabilities and then specified the number of students with LDs ( Richardson, 2015 , 2016 ; Shonfeld and Ronen, 2015 ; Terras et al, 2015 ; Benmarrakchi et al, 2017 ; Sharabi et al, 2016 ; Alamri and Tyler-Wood, 2017 ; Berizzi et al, 2017 ; Kent et al, 2018 ; Lipka et al, 2019 ; Ouherrou et al, 2019 ; García-González et al, 2020 ); while in other papers, the sample is made up only of students with LDs ( Chen et al, 2015 ; Straub and Vasquez, 2015 ; Vasalou et al, 2017 ; Lambert and Dryer, 2018 ). Regarding the level of schooling, about 1/2 of the studies focused on University environments ( Richardson, 2015 , 2016 ; Terras et al, 2015 ; Alamri and Tyler-Wood, 2017 ; Naumova et al, 2017 ; Kent et al, 2018 ; García-González et al, 2020 ) and the other 1/2 examined primary and secondary schools ( Chen et al, 2015 ; Straub and Vasquez, 2015 ; Benmarrakchi et al, 2017 ; Rice and Carter, 2016 ; Smith et al, 2016 ; Adam and Tatnall, 2017 ; Berizzi et al, 2017 ; Vasalou et al, 2017 ; Baharuddin and Dalle, 2019 ; Lipka et al, 2019 ; Ouherrou et al, 2019 ; Ziadat, 2019 ; Nieto-Márquez et al, 2020 ). One paper focused on the transition from school to university ( Sharabi et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…These aspects are reinforced by continuous support of tutors and peers, and reflection on what has been done, the goals to be achieved, and ultimately the strategies to be adopted. Other articles described the possible role of a “universal design for learning approach” in the design of websites, web materials and e-learning platforms ( Chen et al, 2015 ; Shonfeld and Ronen, 2015 ; Alamri and Tyler-Wood, 2017 ; Kent et al, 2018 ; Nieto-Márquez et al, 2020 ) in order to create environments that can be useful also for students with LDs.…”
Section: Resultsmentioning
confidence: 99%